Mutual uncertainty and credible reassurance: experimental evidence. Issue 4 (3rd July 2020) - Yoder, Brandon; Haynes, Kyle
ABSTRACT: Recent theoretical work has suggested that mutual uncertainty of a particular kind can promote credible reassurance and cooperation among states with compatible preferences. Specifically, on issues where cooperation is subjective, such that states are uncertain what types of actions the other will view as cooperative, credible reassurance under mutual uncertainty is straightforward. This finding, if correct, has profound implications for the scope and severity of the security dilemma, suggesting that misplaced suspicion due to uncertainty can be readily overcome under a range of realistic conditions. We present the results of a laboratory experiment testing this important theoretical claim, and find broad support for it. When cooperation is subjective, mutual uncertainty induces senders to signal their true preferences and allows receivers to form more accurate beliefs about the sender's type. Importantly, however, mutual uncertainty did not increase receivers' confidence in their assessments of the sender's type. Thus, receivers responded appropriately as signals became more credible, but failed to recognize that their beliefs had become more accurate. This distinction between the accuracy and confidence of beliefs has broad implications for international relations theory and social science methodology.